Physical and thermal properties of a chitosan/alginate nanolayered PET film - Cunha, M. G. C. (2010)
Nanolaminates have been reported to have applications in different areas, such as the preparation of multilayer films, coating biomedical appliances or multilayer edible coatings with enhanced properties for applications in the food industry. This work aims at characterizing the surface properties, water vapor permeability, and thermal and mechanical properties of a nanolayered film. The film was produced using two polysaccharides with opposite charges, chitosan and sodium alginate deposited on to aminolyzed/charged PET. Contact angle measurements showed differences in the films with a successively higher number of layers. SEM images allowed the measurement of the thickness of the layers. The nanolayered film had a water vapor permeability of (0.85±0.04)×10−11 gm−1 s−1 Pa−1 and a hardness increase of 0.245±0.06 GPa. DSC and TG analyses of the nanolayered film showed increases of 39.2% in the melting energy when compared with the PET film used as support, and a decrease in the decomposition temperature from 386 to 331 ◦C.